2022
DOI: 10.3390/su142416821
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Thermoelectric Generation: A Review

Abstract: The world’s growing energy demand poses several concerns regarding the rational and efficient use of energy resources. This is also the case for many industrial processes, where energy losses and particularly thermal losses are common. Thermoelectric generators offer an alternative to address some of these challenges by recovering wasted heat and thereby increasing the overall efficiency of these processes. However, the successful operation of the thermoelectrical modules meant to carry this process is only po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 141 publications
0
10
0
Order By: Relevance
“…However, we believe that the κ of this film is low for the following reasons: (1) Cu2S has a very low κ of 0.45 W m −1 K −1 [23]. (2) The film contains grains with sizes from nano to submicron, grain boundaries, and heterointerfaces between Cu1.96S and Cu2S grains, which can scatter phonons to lower the κ.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, we believe that the κ of this film is low for the following reasons: (1) Cu2S has a very low κ of 0.45 W m −1 K −1 [23]. (2) The film contains grains with sizes from nano to submicron, grain boundaries, and heterointerfaces between Cu1.96S and Cu2S grains, which can scatter phonons to lower the κ.…”
Section: Resultsmentioning
confidence: 98%
“…Flexible thermoelectrics (TEs) can be used in self-powered technologies and hold promise in wearable sensors and electronics for health and environment monitoring, which has attracted more and more attention in recent years [ 1 , 2 , 3 ]. Flexible TE generators (f-TEGs), which are easily bent to well fit the curved skin surface of the human body, can utilize temperature difference (Δ T ) between the human body and environment based on the Seebeck effect [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lemine et al [15] reported a comprehensive review research highlighting the promising and future-generation TEG devices based on thin film technologies with highly flexible, transparent, non-toxic, plentiful, and light-density p-type Copper Iodide (Cul) thin films. Sanin-Villa [16] reported that research involving carbon nanotubes/polyaniline composite films has found promising results due to its low thermal conductivity.…”
Section: Evolution Of Thermoelectric Materials: From Nanostructures T...mentioning
confidence: 99%
“…Thermoelectric generators (TEGs) are solid-state semiconductor devices that produce a DC power output if a temperature difference exists. The working principle of a thermoelectric generator is based on three basic thermoelectric phenomena, namely, the Seebeck effect [21], the Peltier effect [22], and the Thomson effect [23]. Compared with other methods, a TEG has some inherent advantages, as it is a solid-state device, completely silent, zero-emission, compact, and capable of producing power from any heat source [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%